Features of the State of Internal Organs and the Structure of Comorbidity in Deceased Persons With Alcoholic Liver Cirrhosis, Non-alcoholic Fatty Liver Disease at the Cirrhosis Stage and Alcoholic Liver Cirrhosis Associated With Insulin Resistance and Obesity - N. Matkovska (Львівський клінічний вісник)
Introduction. Today, the most common pathologies among the chronic diffuse liver diseases is non-alcoholic fatty liver disease (NAFLD) and alcoholic liver disease. The aim of the study. The aim of the work was to study the peculiarities of the the state of internal organs in deceased persons with alcoholic liver cirrhosis (ALC), NAFLD at the cirrhosis stage and ALC associated with insulin resistance (IR) and obesity on the basis of analysis of protocols of pathoanatomical research. Materials and methods. 216 protocols of the pathoanatomical study of patients with liver cirrhosis (LC). Among the deceased were: 69 (31.9 %) patients with ALС, 42 (19.4 %) patients with NAFLD at the cirrhosis stage and 105 (48.6 %) persons with ALС associated with IR and obesity. Results. In deceased persons with ALC associated with IR and obesity, it was revealed that disorders of the organs of the digestive, respiratory, urinary, cardiovascular, endocrine and nervous systems were more pronounced. Each deceased with a combination of ALD and IR and obesity at the stage of subcompensation, had more than four, and at the stage of decompensation – more than six concomitant diseases. They had significant systemic atherosclerotic lesions (SAL) of the vascular bed. In 5.3 % of people with ALС associated with IR and obesity, hepatocellular carcinoma was detected. Conclusions. In deceased persons with ALC with IR and obesity the disorders of the organs of the digestive, respiratory, urinary, cardiovascular, endocrine and nervous systems were more pronounced. They had significant SAL of the vascular bed, which led to the development of acute vascular adverse events for one third of people.